WORKSHOP PELUANG USAHA UMKM DAN EKONOMI KREATIF PASCA PANDEMI DESA WALED, KECAMATAN KEMIRI, KABUPATEN PURWOREJO - Setiaji, Cahyo (Jurnal Berdaya Mandiri, 2023)
After the Covid 19 pandemic, the community continued to try to adjust to the New Normal policy, one of which was the people of Waled Village, Kemiri District, Purworejo Regency. The geographical area which is very advantageous has not been able to be used optimally. The community is very dependent on the economy of rice farming. This activity is an effort to introduce the community to potential areas that can be developed as MSME business opportunities while at the same time providing an understanding of the potential for entrepreneurship in the region. Implementation of activities using the method of lectures, discussions, and incidental assistance. The results of community service activities are an increase in understanding of the business potential of MSMEs, an introduction to regional potential, and an understanding of how to start entrepreneurship for the community. MSME actors before the activity numbered 37 increased to 43 people. Business fields that have been licensed have increased from 11 business sectors to 36 businesses that will be processed. Keywords: pandemic, covid 19, SMEs, creative economy